2008
DOI: 10.1007/s10151-008-0425-7
|View full text |Cite
|
Sign up to set email alerts
|

Obliteration of the fistulous tract with BioGlue® adversely affects the outcome of transanal advancement flap repair

Abstract: Our findings indicate that obliteration of the fistulous tract with BioGlue adversely affects the outcome of TAFR for high transsphincteric fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…This phenomenon has not been specifically described in previous studies on AGG, although inflammation and toxic effects were seen [20][21][22], which may trigger this type of pathological tissue integration. Our findings with AGG are analogous to previously published results of cyanoacrylate mesh fixation in the onlay model, where inhibition of tissue integration triggered by the adhesive was seen [12].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This phenomenon has not been specifically described in previous studies on AGG, although inflammation and toxic effects were seen [20][21][22], which may trigger this type of pathological tissue integration. Our findings with AGG are analogous to previously published results of cyanoacrylate mesh fixation in the onlay model, where inhibition of tissue integration triggered by the adhesive was seen [12].…”
Section: Discussionmentioning
confidence: 75%
“…Clinical application of the adhesive in pancreas resection did not reduce incidence of [27]. A study on the use of AGG for the treatment of anal fistula was terminated prematurely because of complications such as discharge of great amounts of purulent liquid and abscess formation [21]. Wound complications were seen after use of AGG in a neurosurgical study [28].…”
Section: Discussionmentioning
confidence: 97%
“…Halverson et al [18] reported an overall healing rate of only 30% in patients who underwent transanal advancement flap repair for persistent rectovaginal fistula. It seems unlikely that the rather poor outcome of flap repair for rectovaginal fistula can be improved by application of glue, since it has been shown recently that obliteration of trans-sphincteric fistulous tracts with Bioglue Ò adversely affects the outcome of flap repair [20]. Based on these data it seems obvious that persistent rectovaginal fistulas are difficult to treat by a transanal advancement repair.…”
Section: Discussionmentioning
confidence: 96%
“…It remains intact for up to 2 years and is then resorbed slowly and replaced by normal tissue without causing a chronic inflammatory state. 7 There has been a lot of interest in less invasive procedure with the introduction of bioprosthetic fistula plug made from porcine intestinal submucosa (Anal Fistula Plug, Cook Surgical, Inc., Bloomington, IN). Although original designed for anal fistulas, has moved into being used for RVFs with success and continues to be evaluated and has been studied in randomized clinical trials comparing surgical versus fistula plug with mixed results.…”
Section: Discussionmentioning
confidence: 99%